Trends in teachers’ attitudes towards inclusive education in the canton of Vaud and their sense of self-efficacy between 2016 and 2022 - Röthlisberger, Tiffanie; Marteau, Frédéric; Valls, Marjorie (Swiss Journal of Educational Research, 2024)
This cross-sectional study’s aim is to examine changes in the attitudes of teachers in the canton of Vaud (Switzerland) towards inclusive education and in their sense of self-efficacy (SSE), before and after the entry into force of the law on special education and the introduction of the 360° concept in 2019. Attitudes and SSE measured among 167 teachers in 2022 were compared with data collected from 306 teachers in 2016. The results indicate that teachers’ attitudes are less positive in 2022 than in 2016 and that their level of SSE is lower, particularly in secondary education. These results provide food for thought on how to support (future) teachers in implementing inclusive education.